Knockdown of Salusin-β Improves Cardiovascular Function in Myocardial Infarction-Induced Chronic Heart Failure Rats. (11th August 2021) - Xu, Yu; Pan, Yan; Wang, Xingxing; Chen, Aidong; Tang, Xinyu; Liu, Xuanxuan; Han, Ying
Abstract : Salusin- β is a biologically active peptide with 20 amino acids that exerts several cardiovascular activity-regulating effects, such as regulating vascular endothelial function and the proliferation of vascular smooth muscle cells. However, the regulatory effects of salusin- β in myocardial infarction-induced chronic heart failure (CHF) are still unknown. The current study is aimed at investigating the effects of silencing salusin- β on endothelial function, cardiac function, vascular and myocardial remodeling, and its underlying signaling pathways in CHF rats induced by coronary artery ligation. CHF and sham-operated (Sham) rats were subjected to tail vein injection of adenoviral vectors encoding salusin- β shRNA or a control-shRNA. The coronary artery (CA), pulmonary artery (PA), and mesenteric artery (MA) were isolated from rats, and isometric tension measurements of arteries were performed. Compared with Sham rats, the plasma salusin- β, leptin and visfatin levels and the salusin- β protein expression levels of CA, PA, and MA were increased, while the acetylcholine- (ACh-) induced endothelium-dependent vascular relaxation of CA, PA, and MA was attenuated significantly in CHF rats and was improved significantly by salusin- β gene knockdown. Salusin- β knockdown also improved cardiac function and vascular and myocardial remodeling, increased endothelial nitric oxide synthase (eNOS) activity and nitric oxide (NO) levels, and decreased NAD(P)H oxidase activity, NOX-2 and NOX-4 expression, and reactive oxygen species (ROS) levels in arteries in CHF rats. The effects of salusin- β knockdown in CHF rats were attenuated significantly by pretreatment with the NOS inhibitor L-NAME. These results indicate that silencing salusin- β contributes to the improvement of endothelial function, cardiac function, and cardiovascular remodeling in CHF by inhibiting NAD(P)H oxidase-ROS generation and activating eNOS-NO production.